L'exploitation du benjoin dans les hautes terres Batak: situation actuelle - Katz, E. (1998)
The article describes the present situation of exploitation, trade and uses of Sumatra benzoin (Styrax spp.) as well as its historical perspective. North Sumatran Batak people exploit this fragrant resin. They use it for medicine, burn it in rituals and tell myths about it. They trade it at the local level, then hand it to ethnic Chinese who trade and transform it in Sumatra, Central Java and Singapore, which is now its main international trading point. Producers and traders have been going through a difficult phase for the last decades. Nevertheless this international trade has been conducted for at least a thousand years and benzoin continues to be used all over the world as incense, flavouring agent, medicine and perfume.